PENGARUH ALOKASI ANGGARAN BIDANG PENANGGULANGAN FAKIR MISKIN DAN ALOKASI ANGGARAN KESEJAHTERAAN SOSIAL TERHADAP KINERJA DINAS SOSIAL PEMERINTAHAN DAERAH SE-JAWA TENGAH TAHUN 2019-2022 - Husain Ismail, M; Andayani, Tutut Dwi; Imtikhanah, Sobrotul; Pangestika L, Asri (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
The study aims to determine the effect of Budget Allocation in the Poor Reduction Sector and Social Welfare Budget Allocation on the Performance of Local Government Social Services throughout Central Java in 2019-2022. This study used the purposive sampling method so that ten regencies and cities in Central Java were obtained that were worthy of research. Tests were performed with simple linear regression analysis using the Windows SPSS 20 program. The t-test results showed that the Budget Allocation for the Poverty Reduction Sector does not affect the Performance of the Social Service for Poverty Reduction. At the same time, the Social Welfare Budget Allocation affects the Performance of the Social Service for Social Welfare Improvement. The coefficient of determination (R square) test results showed that the Social Service for Social Welfare Improvement performance variable is influenced by the Social Welfare Budget Allocation of 12.8. The results of the coefficient of determination (R Square) show that the performance of the Social Office for Poverty Reduction is influenced by the Budget Allocation for Poverty Reduction by 2.9%. In contrast, the rest is influenced by other variables not used in this study. Keywords: Budget Allocation in the Field of Poor Management, Social Welfare Budget Allocation, and Social Service Performance. REFERENSI Abdurahman. (2019). The Relationship between job satisfacion, work-life balance and organizational commitment on employee performance. Ais, R. (2022). Pengaruh Alokasi Anggaran Bidang Penanggulangan Fakir Miskin Terhadap Kinerja Dinas Sosial Pada Pemerintah Daerah Se-Jawa Tengah Tahun 2018-2020. Jurnal Ilmiah Neraca FEB-UMPP. Alviyanzah, F. (2019). Pembangunan nasional yang berhasil apabila pemerintah dan masyarakat saling bersinergi dalam proses pembangunan, termasuk di bidang kesejahteraan sosial untuk menanggulangi kemiskinan. 2019. Chalil, Z. F. (2009). Efektifitas Penanggulangan Fakir Miskin. In Z. F. Chalil, Efektivitas Penanggulangan Fakir Miskin. Jakarta: PT Gelora Aksara Pratama, 2009. Gillin, G. d. (2022, maret jum'at). Definisi Kemiskinan. Retrieved from Definisi Kemiskinan, atmago.com: https://www.atmago.coom/sosial kemiskinan/definisi kemiskinan Hasanah, N. M. (2019). “Peranan Pemerintah Kota Jambi Terhadap pengentasan kemiskinan melalui program UEP (Usaha Ekonomi Produktif) dan KUBE (Kelompok Usaha Bersama). the influnce of budget allocations for poverty alleviation. Kholidah, N., & Hakim, M. R. (2021). Analysis of zakat empowerment in the era of pandemy COVID-19 towards impossible material and spiritual aspects Mustahik. Jurnal Ilmiah Ekonomi Islam, 7(3), 1653-1662. Kholidah, N., & Salma, A. N. (2019). Filantropi kreatif: Pemberdayaan ekonomi umat berbasis zakat produktif pada program 1000 UMKM LAZISMU Kabupaten Pekalongan. Cakrawala: Jurnal Studi Islam, 14(2), 93-101. Mangkunegara. (2017). The Impact of Work Stress and the Work Environment in the Organization: How Job Satisfaction Affects Employee Performance? Journal of Human Resource and Sustainability Studies. Risgiyanti, R., & Hidayah, R. (2020). The role of workplace spirituality in reducing the negative impact of organizational cynicism on job performance. Jurnal Aplikasi Manajemen, 18(4), 692-703. Riswan, R., Suyono, E., & Mafudi, M. (2017). Revitalization model for village unit cooperative in Indonesia. Sosial, W. D. (2022, Februari kamis). Dinas Sosial. Retrieved from Dinas Sosial. Suyono, E., Farooque, O. A., & Riswan, R. (2016). Toward a model of traditional retailers and sellers empowerment in improving competitiveness against modern markets in Banyumas region, Indonesia. DLSU Business and Economics Review, 25(2), 147-165.